2021
DOI: 10.1007/s00284-021-02588-5
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antidiabetic, Antioxidant Activity, and Probiotic Activities of Lactiplantibacillus plantarum and Lacticaseibacillus paracasei Strains

Abstract: Diabetes, a chronic metabolic disorder, is characterized by persistent hyperglycemia. This study aimed to evaluate the hypoglycemic and antioxidant activities of lactic acid bacteria strains isolated from humans and food products and investigate the probiotic properties of the selected four strains. The hypoglycemic activity of the isolated strains was examined by evaluating the α-glucosidase and α-amylase inhibitory activities. The antioxidant activity was measured using the DPPH, ABTS, and FRAP assays. Four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 60 publications
0
10
2
Order By: Relevance
“…Several studies, such as that of Amaretti et al [ 9 ], ascertained such properties for some lactobacilli, including L. plantarum . More recently, Won et al demonstrated the antioxidant activity of L. plantarum and L. paracasei [ 48 ]. Bee honey intrigued the scientific community’s interest as a natural dietary antioxidant [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies, such as that of Amaretti et al [ 9 ], ascertained such properties for some lactobacilli, including L. plantarum . More recently, Won et al demonstrated the antioxidant activity of L. plantarum and L. paracasei [ 48 ]. Bee honey intrigued the scientific community’s interest as a natural dietary antioxidant [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…The study of the DPPH radical‐scavenging activity performed on MRS broth by a different L. plantarum strain evidenced relative antioxidant activities of 76% (Won et al . 2021). Other authors report that the direct antioxidant activity of of LAB ranged values from 20 to 30% (Jeong et al .…”
Section: Resultsmentioning
confidence: 99%
“…These results are in agreement with those of Düz et al [ 34 ] who reported that the highest antioxidant activity exhibited by L. plantarum IH14L was 90.34%, while the lowest percentage (58.38) was recorded with the GH8L strain. In the work of Won et al [ 35 ], the highest DPPH radical scavenging activity was recorded for Lactiplantibacillus plantarum (60%) and Lacticaseibacillus paracasei (75.80%). The antioxidant activity can be explained by the production of cell surface compounds such as strain-produced extracellular polysaccharides and lipoteichoic acid and the existence of enzymes, such as NADH-oxidase, SOD, NADH peroxide and non-heme manganese catalases in LAB bacteria [ 34 , 36 ].…”
Section: Discussionmentioning
confidence: 99%